2016
DOI: 10.1021/acschembio.6b00650
|View full text |Cite
|
Sign up to set email alerts
|

Phenyl Glycolipids with Different Glycosyl Groups Exhibit Marked Differences in Murine and Human iNKT Cell Activation

Abstract: Glycosphingolipids (GSLs) bearing the α-galactosyl headgroup and the acyl chain terminated with a phenyl derivative were found to be more potent than α-galactosyl ceramide (αGalCer) to stimulate both murine and human invariant natural killer T (iNKT) cells and to induce an antibody isotope switch to IgG. In this study, we replaced the galactosyl group with glucose (αGlc) and its fluoro-analogs and found that phenyl GSLs with αGlc (C34-Glc) and its fluoro-analog 6F-C34-Glc were stronger than those with αGal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In the O -glycoside series these phenyl terminated alkanoyl modifications have been shown to markedly increase the potency of cytokine production relative to their hexacosanoyl derivatives. 24,25,26 Therefore, given the remote positions of these two loci, it was surprising that these fatty acid modifications deactivated rather than activated, the C -glycoside 2 . This said, a similar loss in activity in a murine assay was observed when the hexacosanoic acid residue in C -glycosides 3 was replaced with an 8-phenyloctanoyl chain (cf 4 ), although against human iNKT cells, the expected increase in cytokine release was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the O -glycoside series these phenyl terminated alkanoyl modifications have been shown to markedly increase the potency of cytokine production relative to their hexacosanoyl derivatives. 24,25,26 Therefore, given the remote positions of these two loci, it was surprising that these fatty acid modifications deactivated rather than activated, the C -glycoside 2 . This said, a similar loss in activity in a murine assay was observed when the hexacosanoic acid residue in C -glycosides 3 was replaced with an 8-phenyloctanoyl chain (cf 4 ), although against human iNKT cells, the expected increase in cytokine release was observed.…”
Section: Resultsmentioning
confidence: 99%
“…21,22,23 The 11-phenyl- and 11- p -fluorophenyl-undecanoic derivatives 7 and 8 are interesting as the analogous O -glycosides are reported to show much higher Th-1 bias in against both mice and human iNKT cells compared to their hexacosanoic acid derivatives. 24,25,26 Similarly, the nuanced cytokine profiles of C2–4 diastereomers of KRN 7000 and C-KRN 7000 relative to analogues with the natural stereochemistry, in particular the high Th-1 bias of 4-epiC-KRN7000, inspired 9 . 15,1727 The reverse amide 10 is a probe for the binding of the amide residue.…”
Section: Introductionmentioning
confidence: 99%
“…have found that certain a-GluCer analogues with at erminal aromaticr ing in the acyl chain are more potent NKT-stimulators in humans and act as an effective adjuvant for ac arbohydrate vaccine in mice. [32] Zhang and co-workersh ave reported as mall set of phenylcontaining 4"-analogues that are able to stimulate murineNKThybridomas and cytokiner elease by mouse splenocytes. [33] Particularly,t he phenylethyl ether derivative (Ar2-GSL, 6)e xcites the murine immune system in aT h1-polarizing manner.H owever,t oe xplain the observed polarization,the researchers used an in silico model with ah uman instead of am ouse TCR.…”
Section: Introductionmentioning
confidence: 99%
“…However, Wu et al. have found that certain α‐GluCer analogues with a terminal aromatic ring in the acyl chain are more potent NKT‐stimulators in humans and act as an effective adjuvant for a carbohydrate vaccine in mice . Zhang and co‐workers have reported a small set of phenyl‐containing 4“‐analogues that are able to stimulate murine NKT‐hybridomas and cytokine release by mouse splenocytes .…”
Section: Introductionmentioning
confidence: 99%
“…Chimeric H5/1 (cHA fg ) and Monoglycosylated Chimeric H5/1 (cHA mg ). To evaluate the binding activity of antibody elicited by cHA constructs, BALB/c mice were immunized intramuscularly with 20 μg of cHA fg or cHA mg protein adjuvanted with Al(OH) 3 or C34, an analog of α-galactosylceramide (α-GalCer) (14). The mice were immunized at weeks 0, 2, and 4, and HA-induced serum was obtained on days 28 and 42 and measured using enzyme-linked immunosorbent assay (ELISA) with various recombinant HAs (SI Appendix, Fig.…”
Section: Cross-reactivity Of Antisera From Mice Immunized With Fully mentioning
confidence: 99%